Medicinal plants used by 'root doctors', local traditional healers in Bié province, Angola - Novotna, Barbora; Polesny, Zbynek; Pinto-Basto, Maria Fernanda; Van Damme, Patrick; Pudil, Petr; Mazancova, Jana; Duarte, Maria Cristina (Journal of ethnopharmacology, 2020)
ETHNOPHARMACOLOGICAL RELEVANCE: This study is one of the first post-civil war efforts to document traditional botanical knowledge in Bié province, central Angola, in a first step to bring more studies on the use of medicinal plant resources in this area so as to bring new insights into Angolan bio-cultural diversity. AIM OF THE STUDY: Examine the variety of plant species used for medical purposes, as well as characterize their social and cultural values. Also, it is aimed to compare their uses in the studied region with those in Sub-Saharan Africa and report new ethnomedicinal uses. MATERIALS AND METHODS: We documented traditional medicinal plant knowledge among professional herbalists in two areas in Bié province through participatory observation, semi-structured interviews and transect walks. Ethnobotanical information was quantified based on Use Reports to (1) rate traditional knowledge; and (2) determine most useful taxa. RESULTS: In total, 10 traditional healers shared information on their knowledge. A total of 87 plant species distributed among 57 genera and 36 botanical families were documented with Fabaceae being the best-represented family with 18 species, followed by Phyllanthaceae (6), Apocynaceae (5), Asteraceae (5), Rubiaceae (5), Lamiaceae (4), and Ochnaceae (3). Most medicinal plants are usually gathered at a distance from human settlements because of the belief in the higher efficacy of 'wild' plants shared by all herbalists. Roots are the most common plant part used (79%), explaining why the consulted herbalists call themselves 'root doctors'. CONCLUSIONS: The culturally most important medicinal species identified in this study, i.e. Securidaca longepedunculata, Garcinia huillensis, Annona stenophylla, Afzelia quanzensis and Strychnos cocculoides, were previously reported for the same use in neighbouring countries and elsewhere in Africa. Our study also indicates that there are several locally valuable species that have not yet been studied for their medical potential, to name a few: Alvesia rosmarinifolia, Diplorhynchus condylocarpon, Eriosema affine, Paropsia brazzaeana, Rhus squalida, Sclerocroton cornutus or Xylopia tomentosa. Moreover, the ethnomedicinal use of 26 species was reported for the first time to sub-Saharan Africa. CLASSIFICATION: Ethnopharmacological field studies.
Keywords: Ovimbundu; rozhovory jako téma; Ethnobotany; Medicine, African Traditional; Female; Interviews as Topic; Angola; tradiční africká medicína; ženské pohlaví; rostlinné extrakty; lidé; Phytotherapy; etnobotanika; Chokwe; kulturní charakteristiky; léčivé rostliny; Cultural Characteristics; Traditional knowledge; fytoterapie; Male; Plant Roots; Aged; Ethnomedicine; Africa; Health Knowledge, Attitudes, Practice; Plant Extracts; zdraví - znalosti, postoje, praxe; lidé středního věku; senioři; mužské pohlaví; Plants, Medicinal; kořeny rostlin; Middle Aged; Humans